2007
DOI: 10.1089/sur.2006.003
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Vasopressin to Norepinephrine as Independent Predictor of Mortality in Patients with Refractory Septic Shock: An Observational Study

Abstract: "Addition of vasopressin to norepinephrine as independent predictor of mortality in patients with refractory septic shock: An observational study."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Our finding supports an important clinical issue in the practice of intensive care: critically ill patients treated with a very high dose of vasopressor have a very high mortality rate and CRRT may not improve patients' outcome in our cohort.The association between the highest NE dose and morality can be explained by the poor cardiovascular response to catecholamine (5,16). Similar to our finding, previous studies (6,(17)(18)(19) have also shown a high mortality rate in septic shock patients treated with a very high NE dose. More prospective interventional studies are needed to determine if CRRT before very high vasopressor use in critically ill patients improves patient survival.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our finding supports an important clinical issue in the practice of intensive care: critically ill patients treated with a very high dose of vasopressor have a very high mortality rate and CRRT may not improve patients' outcome in our cohort.The association between the highest NE dose and morality can be explained by the poor cardiovascular response to catecholamine (5,16). Similar to our finding, previous studies (6,(17)(18)(19) have also shown a high mortality rate in septic shock patients treated with a very high NE dose. More prospective interventional studies are needed to determine if CRRT before very high vasopressor use in critically ill patients improves patient survival.…”
Section: Discussionsupporting
confidence: 90%
“…The association between the highest NE dose and morality can be explained by the poor cardiovascular response to catecholamine (5,16). Similar to our finding, previous studies (6,17–19) have also shown a high mortality rate in septic shock patients treated with a very high NE dose. More prospective interventional studies are needed to determine if CRRT before very high vasopressor use in critically ill patients improves patient survival.…”
Section: Discussionsupporting
confidence: 90%
“…While the VASST investigators found that a subgroup of patients with less severe septic shock had decreased mortality when treated with vasopressin (AVP 27% vs NE 36%, P = 0.05), the significance of this finding has been questioned, as the subgroup population was not powered for this outcome. In practice, vasopressin has been initiated at different time points with varied results that have mostly been reported in retrospective and small, prospective studies …”
Section: Discussionmentioning
confidence: 99%
“…In practice, vasopressin has been initiated at different time points with varied results that have mostly been reported in retrospective and small, prospective studies. 9,16,17,[20][21][22] All values are presented as median (interquartile range). In July 2015, the standard concentration of vasopressin dispensed at our institution was changed from 60 units/100 mL to 20 units/50 mL.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50][51][52] Two of these deserve an additional comment because they were used in large cohorts of septic shock patients. 50,52 The Sepsis Occurrence in Acutely Ill Patients (SOAP) study was designed to assess the incidence of sepsis and the characteristics of critically ill patients in European ICUs.…”
Section: Observational Studies Of Catecholamines In Septic Shockmentioning
confidence: 99%